Nitric oxide modulates reactivity to angiotensin II in internal mammary arterial grafts in hytertensive patients without associated risk factors - Joo Turoni, Claudio Martín (2011)
We investigated the effects of extraendothelial nitric oxide (NO) on angiotensin II (Ang II) reactivity in internal mammary artery (IMA) rings, as well as the impact of hypertension without associated risk factors in this response. Vascular reactivity, NO levels, and resting membrane potentials were determined in hypertensive (HT) and normotensive (NT) IMA rings. Only rings with endothelial dysfunction were included. Ang II produced a dose-dependent contraction that was higher in HT rings. Response to Ang II was potentiated by Nω-nitro L-arginine methyl ester (L-NAME) in NT but not in HT rings. The antioxidant agents tempol and diphenyleneiodonium (DPI) reverted the hyperreactivity to Ang II in HT rings. Extraendothelial NO was present in both NT and HT rings. However, NT rings showed higher values. LNAME and S-methyl-L-thiocitrulline inhibited NO release in all cases. L-arginine reverted this inhibition. Both tempol and DPI increased NO release in both NT and HT rings. The number of vascular smooth muscle cells (VSMC) and anti-α-actin positive areas were lower in HT than in NT rings, without variations in wall thickness or wall/lumen ratio. With regard to resting membrane potential, we found in HT rings that the depolarization induced by Ang II was abolished by tempol. These findings suggest that extraendothelial NO counterregulates Ang II contractility in IMA rings; however, its action could be altered in hypertensive situations even though the patients did not have associated risk factors. We suggest two mechanisms: increased oxidative stress and a decreased ability of nNOS in VSMC to produce NO.